Advancing Minoritized Learners' STEM Oriented Communication Competency Through a Science Center-Based Summer Program. - Puvirajah, Anton; Verma, Geeta; Campbell, Todd (Journal of Museum Education, 2020)
Grounded on the tenets of informal learning this research took place in a STEM-focused summer youth program at a state science center. We used a research practice partnership to iteratively improve the triggering and development of minoritized learners' STEM identification and interests. Informed by our previous qualitative research that revealed the importance of learner's communication competence as a key focus and driver to gaining confidence, understanding, and supporting their STEM identification, the research reported here drew on a survey strategy to examine the extent to which the summer youth program supported participants' self-perceived communication competence. The findings from the survey revealed that participants' mean overall communication competence level, as well as their communication competence in four different contexts and with three different types of individuals showed significant increase. The findings suggest that providing engaging and meaningful STEM experiences to minoritized underserved learners in a summer program have positive consequences. Such experiences tend to occur more in informal settings and provide learners opportunities to develop STEM-informed agency.